Strategi Intervensi Multidimensi Dalam Pencegahan Jatuh Pada Lansia: A Literature Review - Nurma Zela Gustina (Jurnal Medisains Kesehatan, 2026)
Falls among the elderly represent a significant global public health challenge, directly impacting functional independence and quality of life. This literature review aims to synthesize various fall prevention intervention strategies based on seven recent international studies (2021–2025). The methodology employed is a narrative literature review of articles addressing physical exercise, self-efficacy, risk screening, and religious activities. The review findings indicate that combined interventions—incorporating structured physical exercises (such as the 9-step core exercise), enhancing self-efficacy through the Otago Exercise Program (OEP), implementing risk screening based on the STEADI protocol, and engaging in routine physical-religious activities (such as Salah)—are significantly effective in reducing fall risks. In conclusion, successful fall prevention requires a holistic approach that integrates physical, psychological, and environmental modification aspects.